An Assessment of IFLA/DANIDA Sponsored ILL/DD Project in Ghana - The Users Point of View - Cobblah, Mac-Anthony (Ghana Library Journal, 2002)
The need to assess DANIDA sponsored ILL/DD project in Ghana is justified by the important role it plays in the fulfillment of information provision in the University and Research Libraries in Ghana. The availability of current materials and appropriate services offered by the ILL/DD offices in a congenial atmosphere motivate people to use the libraries for research purpose. The aim of this study is therefore to find out to what extend the available materials and services provided by ILL/DD offices in Gllana are actually satisftjing the needs of the users of those libraries and how effectively they are using those resources. In doing this, the study evaluated the ILL/DD project in Ghana and analysed the impact of the project on the users to es tablish the current performance in terms of fulfilling the needs of the users. In conclusion the study made some sugges tions and recommendations for the development of the ILL/DD project in Ghana.